2016
DOI: 10.15184/aqy.2016.110
|View full text |Cite
|
Sign up to set email alerts
|

Affad 23: settlement structures and palaeoenvironments in the Terminal Pleistocene of the Middle Nile Valley, Sudan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…The Late Pleistocene eastern Afrotropical reduncine record is similar to the Middle Pleistocene with Kobus ellipsiprymnus and Redunca redunca reported from Mumba Shelter (Mehlman, 1979) and the latter from Affad-23 (Osypiński et al, 2016). Both species were also reported at Aduma (Ardu B; Yellen et al, 2005).…”
Section: Reduncinaesupporting
confidence: 69%
See 1 more Smart Citation
“…The Late Pleistocene eastern Afrotropical reduncine record is similar to the Middle Pleistocene with Kobus ellipsiprymnus and Redunca redunca reported from Mumba Shelter (Mehlman, 1979) and the latter from Affad-23 (Osypiński et al, 2016). Both species were also reported at Aduma (Ardu B; Yellen et al, 2005).…”
Section: Reduncinaesupporting
confidence: 69%
“…Lukenya Hill in Kenya has a particularly rich antilopine record and includes Oreotragus oreotragus, Ou. ourebi and Madoqua kirki (Marean and Gifford-Gonzalez, 1991;Marean, 1992) and M. saltiana was found at Affad-23 in Ethiopia (Osypiński et al, 2016). In the Saharo-Arabian region, Gazella dama, G. dorcas and perhaps G. rufifrons were found at Bir Tirfawi (Gautier, 1993).…”
Section: Antilopinaementioning
confidence: 99%
“…The methodology of the Kielce laboratory and the results of measurements from 2014 were published as supplementary materials (Kalicki and Olszak 2016) of the article on geomorphology and remains of settlement from Affad (Osypiński et al . 2016). A total of 12 samples were analysed in this laboratory using the multi‐grain single‐aliquot regenerative (SAR) method on quartz (63–100 μm diameter) and calculating the age of the samples according to the Minimum Age Model (MAM) (as described by Galbraith et al .…”
Section: Summarized Methods and The Results Of Laboratory Analysesmentioning
confidence: 99%
“…Sometimes, however, within buried levels the original elements of the stratigraphy are preserved in‐situ (e.g., at Affad 23), including anthropogenic cut features, such as postholes, hearths and clusters of the levallois/Middle Stone Age (MSA) lithics (Osypiński et al . 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation history of the explored area reconstructed due to present research at Affad 23 revealed accumulation of sand and silt units, dated by OSL method (Kalicki and Olszak 2016) to the period 15.9 ± 1.75 ka (UJK-OSL-35) and 15.1 ± 1.66 (UJK-OSL-37), over calcareous silts of LGM alluviation dated to 21.1 ± 2.32 ka (UJK-OSL-36). Sand bar or channel bank beach was a place of human seasonal settlement.…”
Section: Introductionmentioning
confidence: 88%